2019
DOI: 10.32098/mltj.01.2015.10
|View full text |Cite
|
Sign up to set email alerts
|

Focal Myositis in paediatric age

Abstract: Background: Focal Myositis is a rare pseudotumor of unknown aetiology that is often difficult to diagnose and treat. Typically afflicting people in adulthood, it has occasionally been reported also among children. Purpose: the aim of this study is to review the literature of Focal Myositis in paediatric age in order to compare the clinical manifestation and the various treatment suggested by different authors. Methods: this article describes a 6-year-old boy with focal myositis in gracilis muscle successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…If the motion of the adjacent joint is limited, surgical therapy may be an alternative especially in the case of unclear diagnosis. [ 13 ] Gigante et al [ 14 ] also suggested that conservative methods including medications should be the first choice for FM in pediatric age and that surgery should be strictly reserved for selected cases where noninvasive methods have previously failed. Snell and Dowd [ 15 ] reported a case of recurrent FM presenting as flexion contractures of the fingers which had an over 3-year course.…”
Section: Discussionmentioning
confidence: 99%
“…If the motion of the adjacent joint is limited, surgical therapy may be an alternative especially in the case of unclear diagnosis. [ 13 ] Gigante et al [ 14 ] also suggested that conservative methods including medications should be the first choice for FM in pediatric age and that surgery should be strictly reserved for selected cases where noninvasive methods have previously failed. Snell and Dowd [ 15 ] reported a case of recurrent FM presenting as flexion contractures of the fingers which had an over 3-year course.…”
Section: Discussionmentioning
confidence: 99%